Long-term Survival after resection for perihilar cholangiocarcinoma: Impact of UICC staging and surgical procedure - Juntermanns, Benjamin; Maximillian Kaiser, Gernot; Reis, Henning; Gries, Silvia; Kasper, Stefan; Paul, Andreas; Canbay, Ali; Dominik Fingas, Christian (Turkish Journal of Gastroenterology, 2019)
Abstract Background/Aims: Perihilar cholangiocarcinoma is a rare disease with unfavorable prognosis resulting in low survival rates. This study aims to retrospectively assess the beneficial histopathological features and surgical procedures in long-term survivors (i.e., patients surviving perihilar cholangiocarcinoma for at least 2 y). Material and Methods: In total, 322 patients with perihilar cholangiocarcinoma underwent surgery at our center. The follow-up ended in 2017; 76 patients survived for >2 y. The type of resection, UICC stage, and histopathological features were compared between three survival groups (>2-3, >3-5, and >5 y). Results: The >5-year-survival rate in our selected study cohort was 43.4% (>3-5 y,31.6% and >2-3 y, 25.0%), and 14.5% of the patients survived for >10 y after surgery. Patients with non-regional lymph node positive tumors and/or distant metastasis (i.e., UICC stage IVb; p=0.0112), R2 status (p=0.0288), and exploratory laparotomy only (p=0.0157) showed the poorest survival rates. Perineural invasion had no significant impact on the overall survival. However, 29.0% patients surviving for >5 y displayed the lowest perineural infiltration prevalence. Interestingly, Bismuth-Corlette stage IIIa (p=0.0467), especially caudate lobectomy (p=0.0034), was associated with disease-specific overall survival of >5y. Conclusion: Complete/extended tumor resection with additional caudate lobe resection is strongly associated with long-term survival. Perineural infiltration as a negative prognostic marker for prolonged survival needs to be evaluated in larger study cohorts. Cite this article as: Juntermanns B, Kaiser GM, Reis H, et al. Long-term Survival after resection for perihilar cholangiocarcinoma: Impact of UICC staging and a surgical procedure. Turk J Gastroenterol 2019; 30(5): 454-60.